Investigating the use of YouTube as virtual teaching medium in ELT among non-English students - Adisti, Aprilian Ria (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
Since the COVID-19 pandemic came up suddenly to this world, everything takes a drastic turn. The Ministry of Education and Culture Republic of Indonesia reacted to this issue by making an online learning policy Number 3 of 2020 on Prevention of COVID-19 in the Education Unit. Many education institutions adopted this policy by creating online tools such as YouTube as a resource of transition from face-to-face learning to virtual learning since it is seen as a popular medium used in online classes. This research investigates the use of YouTube as a medium in the English 1 course for non-English students at one of State Islamic University in Salatiga. YouTube is an online learning platform that enables lecturers and students to upload, view, share, and even interact through the comments column in the learning videos. A descriptive qualitative method is used to achieve the objective of the research, which involved three classes from the Early Childhood Islamic Education study program, the Islamic Elementary School study program, and the Islamic Religious Education study program as the objects in this research. The researcher limits the content of YouTube from the channel